Quantifying opponent process dynamics in pornography use and masturbation: An exploratory ecological momentary assessment study - Henry N; Pedersen M; Williams M; Donkin L (Springer, 2025)
The causal relationships between pornography use, masturbation, moral incongruence, and mental health are poorly understood. While the link between problematic pornography use (PPU) and depression is well documented, the temporal dynamics associated with pornography use and masturbation have not yet been quantified. Utilizing an exploratory ecological momentary assessment (EMA) design, we measured the temporal dynamics of cognitive and affective state variables collected from 22 participants before, during, and after pornography use and masturbation, and examined the moderating role of moral incongruence in these relationships. Participants completed an initial survey followed by a four-week EMA, capturing data on sexual activities and cognitive and affective state variables. Bayesian hierarchical mixed-effects models were employed to analyze temporal dynamics. Findings suggest that pornography use and masturbation were linked to changes in affective and cognitive states that spiked both before and after sexual episodes. These states were generally more pronounced and sustained in participants with high moral incongruence, who experienced transient increases in shame, guilt, difficulty thinking, relationship disconnectedness, craving for sexual intercourse, and mood deterioration after pornography use and masturbation. These shifts typically persisted for several hours before decaying to baseline levels. High-incongruence participants also experienced strong spikes in craving prior to sexual episodes, while low-incongruence participants experienced craving spikes after pornography use and masturbation, indicating possible sensitization effects. Our findings also signalled potential evidence for “brain fog” following pornography use in both low and high-incongruence participants. Further, we discovered opponent process dynamics in the mood of high-incongruence participants, providing a possible causal mechanism that may explain how PPU can lead to depression.